Infrared spectroscopy of mixed glass former effect in borotellurite glasses: A review / Nur Ramadhan Mohamad Azaludin and Nurul Syahidah Sabri - Mohamad Azaludin, Nur Ramadhan; Sabri, Nurul Syahidah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Borotellurite (BT) glasses have been extensively studied since the past decades until now because of their worthy properties and for further development in the study of glass. The combination of tellurite and borate network former oxides yields improved physical, optical and electrical features of the glass. BT glass matrix consists of BO4, BO3, TeO4 and TeO3 units. The coordination number of tellurium was altered from four to three through the cleavage of the glassy matrix of tellurite. A review in terms of infrared spectroscopy analysis is performed for identifying the mixed glass former effect (MGFE) in BT glasses with incorporation of different types of dopants. Infrared spectroscopy (IR) revealed various functional groups that are present within the glass samples according to the types of dopants added into the glass system. The effects of different dopants of MGFE in BT glasses that observed from the IR data obtained, are further discussed.